The discerning voter: Party–voter linkages and local distribution under multilevel governance. (March 2020) - Schneider, Mark
What shapes voters' expectations of receiving private benefits and local public goods in developing world democracies? Models of instrumental voting suggest that voters' expectations are shaped by co-partisanship; however, this work does not consider the calculations that voters make in multilevel systems where different types of goods are allocated by different tiers of government. In this article, I argue that voters condition their expectations of private benefits on co-partisan ties with the local leader, but only do so with respect to local public goods when the local leader is aligned with the state government that controls the allocation of pork barrel spending. I test my argument with a vignette experiment conducted in rural India that randomly assigns the partisan affiliation of real village politicians and find empirical support for the argument. I also find suggestive evidence of strategic voting in local elections towards leaders aligned with the ruling party.